The American boom trap - Scott, Peter (Wildfowl, 1952)
The device was first used in December 1948 by Herbert H. Dill and William H. Thornsberry at the Swan Lake National Wildlife Refuge, Sumner, Missouri. They had decided to use a net propelled by projectiles fired from mortars and had begun experiments with it before hearing of the Trust’s rocket-propelled nets. One of the boom traps is controlled by about 400 yards of electric lead from a silo tower, and it had been fired only half an hour before for a catch of thirty-two geese.